Biomass production of Tetraselmis suecica using seawater with sanguaza - Silva B., Juan (2013)
The growth of Tetraselmis suecica was evaluated. The experiment was realized using the Response Surface Methodology (RSM) with Central Composite Rotational Design (CCRD) with two factors, pH and sanguaza/seawater concentration in the range of 7 - 9 and 2 - 5 % (v/v), respectively. The culture media were stirred by bubbling air constantly (0.07 L/s) and continuously illuminated with 40 W of fluorescent light in glass containers of 1.5 L capacity at a temperature of 22.5 ± 2.1 °C. Using the Gompertz mathematical model was determined that from an 8.0 of pH and a ratio of 3.5% of sanguaza/seawater, the Tetraselmis suecica achieves maximum growth. An 8.71 of pH and a ratio of 4.56% of sanguaza/seawater allow the Tetraselmis suecica maximum growth (logN/N0) of 0.659, with a 12.3% of prediction error by applying a mathematical model of 2nd order. According to the study, the values obtained in sanguaza/seawater as a culture medium outperformed the traditionally used culture medium (Guillard F/2 with seawater). The results demonstrate the potential use of the sanguaza/seawater medium in scalable studies on pilot scale production of Tetraselmis suecica, with a view to the production of biodiesel.